Split ileostomy and ileocolostomy for Crohn's disease of the colon and ulcerative colitis: a 20 year survey. - Harper, P; Truelove, S; Lee, E; Kettlewell, MG; Jewell, D (1983)
The clinical course of 140 patients who have had a split ileostomy for ulcerative colitis or colonic Crohn's disease over a 20 year period is reported. In 37 patients with ulcerative colitis there was no sustained improvement. In the 102 patients with Crohn's disease there was an immediate clinical improvement in 95, which was sustained in 65. Thirty patients have subsequently required a proctocolectomy for persistent inflammation, and 28 are still defunctioned. Bowel continuity was restored after 61 split ileostomies and in 44 patients intestinal continuity remains intact at the present time (mean follow up since closure = 62.5 months, range 0-231 months). It is concluded that a split ileostomy is a safe conservative operation producing at least temporary improvement in severely ill and malnourished patients with Crohn's colitis, and that if a subsequent resection becomes necessary it may be less extensive than was thought applicable at the initial operation. In 27 patients a resection has not been required.